Need, risk and protection in social work practice - Hothersall, Steve J.; Maas-Lowit, Mike (Exeter : Learning Matters Ltd., 2010)
This book provides a general introduction to working with risk in social care.
Cover; Title; Copyright; Contents; Notes on contributors; Introduction; Part One; 1 Need and vulnerability; 2 Risk; 3 Protection; 4 Capacity and incapacity; Part Two; 5 Need, risk and protection in work with children, young people and their families; 6 Mental health; 7 Older people; 8 Need, risk and protection in criminal justice social work and probation; 9 Need, risk and disability; 10 Substance use: What are the risks?; Conclusion; References; Index; A; B; C; D; E; F; G; H; I; K; L; M; N; O; P; R; S; T; U; V; W; Y.
Includes bibliographical references and index.
Print version record.
Keywords: Social service -- Great Britain -- Case studies; Social service -- Great Britain; United Kingdom; Case studies